Knowledge, Moral Attitude, and Practice of Nursing Students Toward Abortion - Sutira Uaamnuichai MD; Rattiya Chuchot MNS; Phanupong Phutrakool PhD; Ratthapong Rongkapich; Rada Poolkumlung; Somsook Santibenchakul MD; Unnop Jaisamrarn MD (SAGE Publishing, 2023)
In 2021, Thailand decriminalized abortions to allow for legal abortions on request up to 12 weeks' gestation and conditionally up to 20 weeks' gestation, or in the case of sexual assault, maternal mental or physical harm, or fetal abnormality. We intend to say that healthcare practitioners' positive attitudes toward abortion will destigmatize abortion for both themselves and their patients. We explored the knowledge, attitudes, and intended practices of nursing students toward safe abortion practices in light of the recent law reform. This was a cross-sectional study using a self-administered questionnaire. The questionnaire consisted of 4 parts: a demographic information questionnaire; and measures to assess their knowledge, moral attitudes, and intended practice regarding safe abortion care. Questionnaires were sent to 206 nursing students who had completed the Midwifery and Maternal-Newborn Nursing rotation in Bangkok, Thailand. The survey response rate was 90.8%. Mean (standard deviation) knowledge score was 6.72 (1.86) out of 10. Buddhist students were more likely to have a positive attitude toward abortions. Most students intended to practice safe abortions in pregnancies that affect maternal physical or mental health, or in pregnancies that resulted from unlawful sexual contact. Students were more ambivalent toward abortion practices for socioeconomic reasons. Better knowledge of abortion legislation was associated with a more positive attitude toward abortions and safe abortion practice intention. Approximately 1 year after the abortion law reform in Thailand, nursing students had incomplete knowledge of the amendment. Most students were inclined to provide abortion care services for certain conditions.